Evaluation of antioxidant status and lipid peroxidation in dogs with myxomatous mitral valve degeneration stage B1 - Tomsič, Katerina; Domanjko Petrič, Aleksandra; Nemec, Ana; Pirman, Tatjana; Rezar, Vida; Seliškar, Alenka; Vovk, Tomaž; Nemec Svete, Alenka (Frontiers in Veterinary Science, 2023)
Myxomatous mitral valve degeneration (MMVD) is the most common naturally occurring heart disease in dogs. There is a lack of data on antioxidant status and oxidative damage in dogs with MMVD stage B1 according to the American College of Veterinary Internal Medicine (ACVIM B1). The aim of this study was to investigate antioxidant status (plasma vitamin E, lipid-standardized vitamin E (LS-VitE), antioxidant capacity of lipid-(ACL) and water-soluble antioxidants, whole blood glutathione peroxidase and erythrocyte superoxide dismutase), and lipid peroxidation (malondialdehyde (MDA)) in dogs with MMVD ACVIM B1. Serum cholesterol and triglyceride concentrations were measured to calculate LS-VitE. Fourteen dogs with MMVD ACVIM B1 and 12 control dogs were included in the study. Dogs with MMVD had significantly higher vitamin E, ACL, MDA, and cholesterol concentrations and significantly higher LS-VitE values than control dogs. No significant correlations between MDA and antioxidant parameters were determined in either group. In conclusion, oxidative damage to lipids is already present and the antioxidant status is altered but not depleted in dogs with MMVD ACVIM B1. The antioxidant response to increased oxidative damage consists mainly of the activation of fat-soluble antioxidants. Further research is needed to evaluate the efficacy and targets of early antioxidant supplementation to prevent or ameliorate oxidative stress and mitigate disease progression in dogs with early-stage MMVD.